SIFAT ORGANOLEPTIK PERMEN JELLY MANGGA KUINI (Mangifera odorata Griff) DENGAN VARIASI KONSENTRASI SIRUP GLUKOSA DAN GELATIN - Sachlan, Putri A. A. U.; Mandey, Lucia Cecilia; Langi, Tineke M. (Fakultas Pertanian, Universitas Sam Ratulangi, 2019)
ABSTRACTThe aims of this reaserch are to determine the right combination of glucose syrup and gelatin, to analyze the physical and chemical components and to evaluate the preference level of the panelists in kuini mango jelly candy. This research has used factorials RAL method with 2 factors, which A factor is glucose syrup concentration and B factor is gelatin concentration. The result of the research found that A3B3 samples that contain 50% of glucose syrup and 25% of gelatin were the most preferred sample by panelist. In conclusion, mostly panelists prefer the sweetest and the hardest sample.Â Keywords: kuini mango, glucose syrup, gelatine, jelly candy